PENGARUH PENERAPAN AKUNTANSI ZAKAT DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PENGELOLAAN ZAKAT PADA BAZNAS KABUPATEN AGAM - Aini, Haniva Khuratul; Rd. Amar Muslih; Ridwan Effendi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research is motivated by the importance of accountability and transparency in zakat management by zakat institutions. Although the potential for zakat in Indonesia is quite large, the level of public trust and participation in distributing zakat through official institutions is not optimal. This is partly influenced by the quality of financial reports presented by zakat management institutions. BAZNAS Agam Regency, as the official institution tasked with collecting and distributing zakat funds, is required to prepare quality financial reports in accordance with applicable zakat accounting standards. Therefore, the implementation of zakat accounting and internal control systems are important factors in improving the quality of zakat management financial reports. This study aims to analyze the extent of the influence of the implementation of zakat accounting and internal control systems on the quality of zakat management financial reports at BAZNAS Agam Regency, both partially and simultaneously. This study uses a quantitative approach with a descriptive method. Data were obtained by distributing questionnaires to respondents related to zakat management at BAZNAS Agam Regency. The collected data were analyzed using multiple linear regression analysis techniques with the help of statistics to determine the effect of independent variables on the dependent variable. The results of the study indicate that the implementation of zakat accounting and internal control systems significantly influence the quality of zakat management financial reports. Simultaneously, both variables contribute to the quality of financial reports with an Adjusted R Square of 0.422 or 42.2%, while the remaining 57.8% is influenced by other variables not examined in this study. These findings indicate that the implementation of good zakat accounting and an effective internal control system can improve the quality of financial reports in zakat institutions.